Madness and free association in Evelyne Mpoudi Ngolle's sous la cendre le feu (2007)
Psychoanalytic insight facilitates the analysis of works of art through which literary analysts are able to access the psyche of authors and their characters. (M.M. Schwartz and D. Willbem: 1982). One of such psychoanalytic devices is free association. Free association technique applied during psychotherapy sessions provides a royal road into the psyche of humans as can be observed in Mina's case in Mpoudi Ngolle's Sous la cendre lefeu. This paper concludes that repression of negative and unpleasant experiences lived within patriarchal limitations, as promoted by African male hegemonic traditions, subjects women-victim of oppression to anxiety disorder which may occur in the form of depression, schizophrenia, obsessive disorders, depersonalisation, derealisation among others.